2015
DOI: 10.1590/0047-2085000000063
|View full text |Cite
|
Sign up to set email alerts
|

Associação de sintomas depressivos e ansiosos com gravidade da migrânea

Abstract: Objetivo O objetivo do presente estudo foi avaliar a associação do sono, depressão e ansiedade em pacientes com migrânea. Métodos Cinquenta pacientes do sexo feminino, provenientes de um centro terciário de tratamento de cefaleias, com o diagnóstico de migrânea segundo os critérios da International Headache Society, foram incluídas neste estudo. As pacientes foram avaliadas com os seguintes instrumentos: Migraine Disability Assessment test (MIDAS), Headache Impact Test (HIT), Hospital Anxiety (HADS-A) and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
2
0
0
5
Order By: Relevance
“…22,23 When the quality of sleep was evaluated, the proportion of "poor sleep" was higher and significant for migraineaffected individuals, who were more likely to be in this category, attuned to a previous study that mentions an association between depression and sleep disorders in headache-affected patients. 20 When analyzing the contributions of catastrophic headaches associated with other clinical conditions, in this study, we confirmed the significance of catastrophization as a strong positive predictor in the occurrence of migraine, which is in line with previous studies. 5,7 Also, associations with other clinical conditions may potentiate functional disability, contributing to deteriorated suffering in times of crisis or those preceding it.…”
Section: (C) (D)supporting
confidence: 92%
See 1 more Smart Citation
“…22,23 When the quality of sleep was evaluated, the proportion of "poor sleep" was higher and significant for migraineaffected individuals, who were more likely to be in this category, attuned to a previous study that mentions an association between depression and sleep disorders in headache-affected patients. 20 When analyzing the contributions of catastrophic headaches associated with other clinical conditions, in this study, we confirmed the significance of catastrophization as a strong positive predictor in the occurrence of migraine, which is in line with previous studies. 5,7 Also, associations with other clinical conditions may potentiate functional disability, contributing to deteriorated suffering in times of crisis or those preceding it.…”
Section: (C) (D)supporting
confidence: 92%
“…Headache catastrophization and its relationship with disability, depression, anxiety, stress and sleep quality between these variables may contribute indirectly to physical disability. 1,3,[5][6][7]20 Women were more affected by migraine in this study and were more likely to have this condition than men, which corroborates most authors in previous studies. 21,22 The significant involvement of women can be partially explained by hormonal factors, in which headache plays an important role and is often potentiated and incapacitating in specific periods of the menstrual cycle.…”
Section: (C) (D)supporting
confidence: 92%
“…Tem-se reconhecido os fatores desencadeantes como aqueles que podem precipitar uma crise álgica e, entre os possíveis, incluem-se o consumo de determinados alimentos, bem como a menstruação, a fadiga, o estresse e as alterações no sono. (3,4) O diagnóstico é essencialmente clínico e não há indicações de exames subsidiários, pois há particularidade clínica na enxaqueca, assim como nas cefaleias primárias, de ser recorrente e estereotipada, o que, em geral, não ocorre nas secundárias, e tal fato foi primordial para o estabelecimento de critérios diagnósticos. A partir das características da dor é possível firmar o diagnóstico em enxaqueca sem ou com aura.…”
Section: Introductionunclassified
“…A partir das características da dor é possível firmar o diagnóstico em enxaqueca sem ou com aura. (4,5) A enxaqueca deve ser considerada um problema de saúde pública, pois, além de ser uma doença crônica, tem elevado grau de incapacidade e sofrimento, sendo seguramente a causa mais frequente de afastamento do trabalho, gerando ônus à sociedade. (6) Essa interferência é marcante quando se trata de estudantes de medicina que são adultos jovens sujeitos a diversos fatores desencadeantes, considerando que a vida acadêmica é cercada de estresse com a grande quantidade de informações para aprender, carga horária integral, necessidade de atividades extracurriculares, cobranças constantes dos amigos e familiares, bem como a obrigatoriedade de estágios em regime de plantão, o que altera o padrão de sono.…”
Section: Introductionunclassified
“…(MACHADO et al, 2022). Apesar dessa prevalência alta, a fisiopatologia da enxaqueca ainda não é completamente compreendida e pode estar relacionada a diversos fatores etiológicos, como estresse, menstruação, fadiga, alterações no sono, alimentos com potencial alergênico, desequilíbrios neuroendócrinos e deficiências nutricionais (QUEIROZ & SILVA JUNIOR, 2015;RAMOS et al, 2015;CAMPANA, et al 2012).…”
unclassified